Question Number 154476 by SANOGO last updated on 18/Sep/21
![soit:y′′−3y′−4y=3e^(3x ) avec , f(o)=−(1/2) et f′(0)=4 alors f(1)=?](https://www.tinkutara.com/question/Q154476.png)
$${soit}:{y}''−\mathrm{3}{y}'−\mathrm{4}{y}=\mathrm{3}{e}^{\mathrm{3}{x}\:} \:{avec}\:, \\ $$$${f}\left({o}\right)=−\frac{\mathrm{1}}{\mathrm{2}}\:{et}\:{f}'\left(\mathrm{0}\right)=\mathrm{4} \\ $$$${alors}\:{f}\left(\mathrm{1}\right)=? \\ $$$$ \\ $$
Answered by ARUNG_Brandon_MBU last updated on 18/Sep/21
![y′′−3y′−4y=3e^(3x) Solution de l′e^](https://www.tinkutara.com/question/Q154481.png)